Does spiritual and religious orientation impact the clinical practice of healthcare providers?. Issue 4 (3rd July 2020) - Palmer Kelly, Elizabeth; Hyer, Madison; Payne, Nicolette; Pawlik, Timothy M.
ABSTRACT: The objective of the current study was to assess the religious and spiritual (R&S) beliefs and practices among healthcare providers, compare R&S among provider types, as well as examine the potential relationship between organized/nonorganized religious activities and intrinsic religiosity with the incorporation of R&S into clinical practice. A cross-sectional descriptive online survey methodology was used. There were 387 participants with an average age of 45.5 years. Providers included primary care providers (26.9%), nurses (27.1%), allied health (23.5%), and mental health professionals (22.5%). Most participants reported being "religious and spiritual" (42.9%) or "spiritual and not religious" (36.6%). There was a difference in R&S among provider types (x2(6) = 12.6, p = .05) with mental health providers more often identifying as spiritual, but not religious (46.6%) compared with other providers. No mental health professional indicated almost always/often/sometimes praying with patients versus 9.5% of primary providers, 14.8% of allied providers, and 18.1% of nurses. Results from structural equation modeling showed that intrinsic religiosity was most strongly associated with how a provider interacted with patients around R&S (β = .644, p < .001) followed by non-organized religious activities (β = .228, p < .001) and organized religious activities (β = .092, p = .037). Understanding the role of R&S beliefs and behaviors of healthcare providers is important to patient-centered care.